Influence of Sowing Techniques, Timing of Herbicide Application and on Weed Infestation and Yield of Rice in Southern Guinea Savannah of Nigeria - Audu, S.D; Haruna, I. M; Ibrahim, A. J; Gbedeyan, S . T; Ibrahim, S O; Bakare, S O (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Field trial was conducted at the research field of National Cereals Research Institutes Badeggi experimental field, Niger state located at (latitude 9o041 02.05’’N and longitude 0.6o011 3.31’’E) and Bacita located at (latitude 9o1 16’N and longitude 5o59’E) both in the Southern Guinea Savannah Agro Ecological Zone of Nigeria during the wet season of 2021 and 2022. To determine the best combination of sowing techniques and time of herbicide application for optimizing rice yield while minimizing weed infestation and crop injury in the Southern Guinea Savannah of Nigeria. The experiment consists of five sowing methods (broadcasting dry, broadcasting wet, dibbling wet, dibbling dry, and transplanting) and two herbicide application timings (2 and 3 weeks after sowing) were tested in a factorial experiment. Data were collected on weed count before herbicide application, weed count at harvest and grain yield per hectare. The result indicated that the Transplanting technique of sowing significantly improved rice productivity in the study area at both seasons, less weed infestation at harvest was recorded with transplanted methods compared to other panting techniques, herbicide application at early growth stage of 2 weeks after sowing (2WAS) promote healthy crop growth and minimize weed competition